GLI1/2-altered mesenchymal tumors: a study of 8 cases expanding the clinicopathological and molecular spectrum including an upstream PTCH1-inactivating mutation - Hiemcke-Jiwa, Laura; van Ewijk, R.; van Noesel, M. M.; Tops, B. B. J.; Koppes, S. A.; Lubeek, S. F. K.; Jonges, G. N.; Witkamp, A. J.; Deimling, Andreas von; Cleven, A. H. G.; Kester, L. A.; Flucke, U. (Virchows Archiv, 2025)
GLI1/2 alterations drive mesenchymal tumors harboring rearrangements and amplifications. Affected patients show a broad age range and tumor distribution, and histology varies. We describe the clinicopathologic and molecular characteristics of eight cases (7 females, 1 male, age range 15-82 years). Tumors were located in the ovary (n = 3), endometrium (n = 1), retroperitoneum (n = 1), skin (n = 1), neck (n = 1), and hypopharynx (n = 1). The cases showed epithelioid (n = 2), spindle cell (n = 1), biphasic (n = 1), or round cell (n = 3) morphology. Two of the latter neoplasms had a prominent myxoid stroma. One tumor was polymorphic with brisk mitotic activity. Immunohistochemistry demonstrated variable positivity for S100,  pankeratin AE1/3, EMA, CD56, synaptophysin and chromogranin. MDM2, CDK4, and STAT6 expressions were detected in cases with GLI1 amplification. In three neoplasms, a fusion gene was identified (GLI1::MALAT1, n = 2; PTBP1::GLI2, n = 1). Three cases harbored GLI1-amplification, with co-amplification of MDM2/CDK4 in two of them. GLI2 was amplified in one tumor. Another case had an inactivating PTCH1 mutation. By RNA expression and DNA methylation profiling, the cases formed a cluster. GLI-amplified tumors occurred in older patients (n = 3) who died within 3-27 months. GLI-fusion genes and the PTCH1 mutation were identified in neoplasms of younger patients (n = 3) remaining disease-free (25-31 months). In conclusion, our GLI1/2 altered mesenchymal tumors, clustered at RNA level and epigenetically, confirming that they form one entity, including neoplasms with PTCH1 mutations. Amplified tumors occurred in older patients and behaved more aggressively, in contrast to lesions with a fusion gene originating in younger patients and showing a favorable outcome.
Online veröffentlicht: 14. August 2025
Gesehen am 20.01.2026